Controversial Issues in Law No. 23 of 2011 on Zakat Management: A Perspective from John Rawls’ Theory of Justice - Saifuddin Saifuddin; Kharisma Wardhatul Khusniah; Naela Rosita; Abdullah Farooqi; Geri Rama (Institute of Multidisciplinary Research and Community Service, 2026)
Law Number 23 of 2011 concerning Zakat Management was enacted to modernize zakat governance and maximize its efficient and effective utilization through constitutional means. However, from a legal standpoint, the law contains controversial provisions that could grant the National Zakat Agency (BAZNAS) authority and supremacy. This study aims to examine these controversial provisions in Law Number 23 of 2011 and evaluate the resulting inequities through the lens of John Rawls's theory of justice. This is a normative legal study employing both statutory and conceptual approaches. The statutory approach was used to identify problematic articles within the law. In contrast, the conceptual approach is used to evaluate and propose a reconstruction of zakat provisions based on Rawlsian justice. Data collection was conducted through a literature review. The findings indicate that Law Number 23 of 2011 grants BAZNAS supreme authority by positioning it simultaneously as a regulator, auditor, and operator. This concentration of power can trigger conflicts of interest and competition with private zakat institutions (LAZ), and even lead to human rights violations by criminalizing zakat administrators (amil) who lack a permit from the Ministry of Religious Affairs. This arrangement contradicts John Rawls's principles of justice, as it restricts fundamental freedoms regarding religious expression and denies private zakat institutions (LAZ) equal opportunity to operate on par with BAZNAS. The distribution of authority outlined in the law fails to ensure substantive justice for the most vulnerable stakeholders in the zakat sector, such as traditional zakat administrators. These findings are reinforced by the Constitutional Court's ruling (Number 97/PUU-XXII/2024), which calls for legal amendments and revisions to achieve